Nursing Students Learn Online Interprofessional Education on Substance Use. Issue 1 (March 2020) - Puskar, Kathy; Mitchell, Ann M.; Lee, Heeyoung; Kane, Irene; Albrecht, Susan A.; Frank, Linda R.; Hagle, Holly; Lindsay, Dawn; Kameg, Brayden; Johnson, Cortney; Sun, Ran
Background: Interprofessional education strategies are becoming more prevalent as nursing schools integrate interprofessional practice activities into their curricula. Purpose: This paper presents the results of a federally funded project to deliver online interprofessional education to nursing students on screening for alcohol and substance use in rural areas, in which their perceptions about interprofessional education were measured. Methods: A quasi-experimental within-subjects repeated measures design was utilized. Students in the bachelor or associate degree program were recruited from two rural nursing schools. A demographic questionnaire, Alcohol and Alcohol Problems Questionnaire, Drug and Drug Problems Questionnaire, and Interprofessional Education Perception Scale were utilized. General linear modeling was used to determine changes in these measurements over time. Data collection was performed at pretraining, posttraining, and following an online interprofessional dialogue. Results: The study consisted of 89 nursing students. The participants were 87% female (n = 77/89) and 91% white (n = 81/89); their mean age was 24.9 years (standard deviation = 10.36). Analysis of evaluation questionnaires demonstrated increased levels of confidence in working with patients who consume alcohol or other drugs and on certain aspects of interprofessional education. Conclusion: Online interprofessional preservice education holds the potential to positively increase nursing students' confidence in working with patients and to increase their interprofessional practice.